Effect of hydroxylated solvents on the active constituents of Salvadora persica root "Siwak" - Maged S. Abdel-Kader; Khalid S. Al Shahrani; Mohammed H. Alqarni; Mohammed A. Salkini; Elsadig H. Khamis; Hazem A. Ghabbour; Saleh I. Alqasoumi (Elsevier, 2019)
Previously, the antimicrobial activity of Salvadora persica was traced to benzyl isothiocyanate. In the present study known inactive compounds were isolated from extracts obtained by different solvents including β-amyrin, β-sitosterol, stigmasterol glucoside, benzyl cyanide and sulphur. However, some inactive compounds were present only in the ethanol and methanol extracts. This observation indicated that these compounds most likely are artifacts resulted from interaction with the solvents used in extraction. Pure benzyl isothiocyanate was kept with different solvents for 72 h and after TLC study they were heated under reflux for 8 h to explore the possibility of interactions. Only solvents with OH groups reacted with benzyl isothiocyanate and gave products similar to those isolated from the alcohol extracts. In conclusion extraction of S. persica with hydroxylated solvents will alter the structure of the active compound benzyl isothiocyanate and leads to loss of antimicrobial activity. Keywords: Salvadora persica, Benzyl isothiocyanate, Solvents effect